Pengaruh Sertifikasi Halal MUI Pada Produk J.CO DONUTS Terhadap Keputusan Pembelian (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara) - Satria Abdillah Ilman; Purnama Ramadhani Silalahi; Khairina Tambunan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study is to determine the effect of halal certification on consumer purchasing decisions in a case study of the C.JO business. The method used in this research is qualitative method. The sampling technique used was the distribution of questionnaires. The results of this study are that halal certification has a significant effect on consumer purchasing decisions where the understanding of students of the Faculty of Economics & Islamic Business on Halal Products in general, reaches 70% of students who will consider purchasing products that do not have a halal label. The majority of Islamic businesses have a good understanding of Halal Food Products.